Reading literature prescribed by the school curricula : pleasure or a nightmare? - Tuđman, Miroslav (2005)
In this paper we presented a new approach to obligatory literature prescribed by the school curricula based on the new literacy and new technologies. We introduced the animation method in teaching and idea of the Web portal of the obligatory literature. We brought the survey of the pupils' current reading interests and explained the challenges of the new multimedia literacy. Also, we introduced multimedia to the classroom and obtained improvement in pupils' language and reading skills. Finally, we believe that understanding and systematic application of the proposed methods can result in better situation regarding the development of pupils' reading interests and language skills.